(431) manpower requirements for the U.A.R. for the period 1960-1985 متطلبات القوى العاملة لجمهورية أرمينيا المتحدة للفترة 1960-1985 - hamdy, mostafa (the institute of national planning, 2018)
This study investigates manpower requirements in the United Arab Republic (U.A.R.) during the period from 1960 to 1985 within the broader framework of long-term national economic and social development planning. The research is based on the premise that scientific manpower planning constitutes a fundamental component of development strategies, as sustainable economic growth largely depends on the availability of human resources in both quantitative and qualitative terms across various sectors of the economy. The study adopted an analytical and forecasting methodology designed to establish long-term projections of demographic and economic variables and to relate these projections to labor market requirements. The research was conducted through successive stages involving the collection and analysis of statistical data and the development of quantitative models for estimating future labor demand. Particular emphasis was placed on examining the relationship between economic growth, demographic trends, labor productivity, and structural changes within the national economy. The research included estimates of national income distributed among major economic sectors, including agriculture, industry, and services, while assessing the contribution of each sector to overall economic activity during the projected period. Furthermore, the study analyzed population trends and labor force supply according to gender and occupational composition. It also estimated labor productivity levels across different sectors and examined their influence on future labor requirements. The findings suggest that anticipated economic changes would generate structural transformations in labor market patterns, creating a need for substantial adjustments in educational and vocational training policies to meet future skill requirements. The study further emphasizes that effective manpower planning depends on the availability of reliable statistical databases and flexible forecasting methods capable of responding to changing economic and social conditions. It concludes that integrating economic development policies with educational and manpower planning strategies is essential for achieving efficient utilization of human resources and supporting long-term development objectives.